Morfologia e anatomia da semente de Esenbeckia grandiflora Mart. (rutaceae) - Da Silva, Linda Lacerda; Paoli, Adelita Aparecida Sartori [UNESP] (My University, 2006)
The morphology and anatomy of the seeds of Esenbeckia grandiflora Mart. were described and illustrated, emphasizing the seed coat and development. The seeds are ellipsoid to pyramidal, brown, anatropous, mesotestal, without inner integument, exarillate and exalbuminous. The embryo is axial, straight, white, with fleshy cotyledons containing protein and lipid storage and it has a short hipocotyl-radicule axis and small plumule.
Morphology and anatomy of Esenbeckia grandiflora Mart. seeds (Rutaceae)
Keywords: Forestry species; Morphological and anatomical studies